UPDATING THE "SPORT" SUBJECT CURRICULUM FOR STUDENTS IN THE SPECIALTIES "NURSE" AND "MIDWIFE" AT THE FACULTY OF PUBLIC HEALTH, MU – SOFIA - K. Gerasimov; A. Bozhkova (Trakia Journal of Sciences)
The discipline "Sport" is a necessary part of the students' education. It regulates the physical with the mental load, improves the motor skills and habits, preserves and improves their health and physical capacity. The training of students in the discipline "Sport" should be focused on their specific professional activity, using different types of sports for stable and sustainable motor, intellectual and emotional development of the personality of the trainers. The aim is to update the curriculum in the discipline "Sport" by including theoretical training (seminars) and additional sports disciplines (Exercises). Tasks: • Analysis of the current curriculum in the discipline "Sports" for students majoring in "Nurse" and "Midwife" from the Faculty of Public Health (FPH) at MU - Sofia. • Inclusion of theoretical material with current topics and a program of activities for independent preparation in the form of seminars. • Inclusion of additional sports disciplines with the appropriate methodology and content to the ones practiced so far. • Expected results. The new additions to the program will help to acquire specialized knowledge about physical exercises, application of exercises for therapeutic purposes, knowledge to practice different types of physical activity and their benefits for maintaining and developing the necessary motor skills of students to practice the professions "Nurse" and "Midwife".